(untitled) (UNED Research Journal, 2024)
Introduction: Ficus pumila and Phtirusa stelis are emerging as a source of natural products. Objectives: Identify the families of chemical compounds present in the species to be studied. Determine the antibacterial and antifungal activity of the crude extracts of F. pumila and P. stelis. Assess the toxicity of the crude extracts of the species against Artemia sp. Determine effects on Aedes aegypti larvae and. Methods: We evaluated the bioactivity of ethanolic, and isopropyl extracts obtained from the fruits, leaves and stems of both species were evaluated for antibacterial activity, antifungal activity, toxic activity against Artemia sp, A. aegypti larvae and phytochemical study. Results: We identificated flavonoids, tannins, and polyphenols in isopropyl and ethanol extracts of leaves, stems and fruits of F. pumila. We detected flavonoids, tannins, anthraquinones, triterpenes, and polyphenols in isopropyl and ethanol extracts of stems and leaves of P. stelis. We detected flavonoids, tannins, anthraquinones, triterpenes, and polyphenols in isopropyl and ethanol extracts of stems and leaves of P. stelis. F. pumila, the isopropyl stem extract demonstrated the most effective activity, since it exerted antibacterial activity, with inhibition halos being observed on B. subtilis (10 mm) and E. coli (7 mm), while the ethanolic extract of the leaves showed effect on Staphylococcus aureus (11 mm). The ethanolic extract of P. stelis leaves exhibited activity against S. aureus (10 mm), B. subtilis (10 mm) and that of stem extract showed similar results with inhibition zone of halos of 11 and 10 mm, respectively. The isopropyl extract of leaves also displayed activity against E. coli (15 mm). None of the extracts from F. pumila and P. stelis, showed any growth inhibitory effect against the pathogenic fungi. The majority of P. stelis extracts showed positive LC results against Artemia sp., with the ethanolic leaf extract exhibiting high toxicity (0,01 µg/mL). The isopropyl leaf extract also showed high toxicity (0,01 µg/mL), as did the isopropyl stem extract (0,02 µg/mL). The ethanolic and isopropyl extracts of F. pumila and P. stelis did not show toxicity to Aedes aegypti larvae. Conclusion: The plant species F. pumila and P. stelis, can be considered as sources of important and promising compounds for therapeutic research. These plants have shown potential in various studies, and further research could lead to the discovery of new treatments and therapies.